Effort-induced headache and blurred vision in a young professional soccer player - Golan, R. (The 3rd Wingate Congress of Exercise and Sport Sciences, 2014)
A 19.5 year old, otherwise healthy soccer player came to our clinic with a major complaint of repeated occipital headaches and blurred vision, during late phases of the game, for about a year. He was advised to rest between training sessions, and continued to train and play as usual. As his symptomatology became more frequent and disturbing, his coach brought him to our clinic for a sports medicine consultation. The coach also raised the question whether this player could safely return to his training and game schedule.